Detection of Escherichia coli and Shigella spp. in water by using the polymerase chain reaction and gene probes for uid. - Bej, A K (1991)
A method was developed for the detection of the fecal coliform bacterium Escherichia coli, using the polymerase chain reaction and gene probes, based on amplifying regions of the uid gene that code for beta-glucuronidase, expression of which forms the basis for fecal coliform detection by the commercially available Colilert method. Amplification and gene probe detection of four different regions of uid specifically detected E. coli and Shigella species, including beta-glucuronidase-negative strains of E. coli; no amplification was observed for other coliform and nonenteric bacteria.